The effect of zimmer twins as digital storytelling on students’ writing narrative text - Dyah Wulandari; Siti Maria Ulfa; Arfiyan Ridwan (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
The objective of the research to compare of Zimmer twins website tool as digital storytelling than use nondigital in writing text narrative on students writing ability at the eleventh grade of MA  Yayasan Sirojul  Islam Sukolilo 2018/2019 academic year. Zimmer twins media is an animated movie maker based on the website for the students to create their short stories in movies with many emotion, etc. The sample of this research the Eleventh of MA YASI those are XI- 1 class as the experimental class, and the X1-2 class as the control class consisted of 20 students. The method in this research was a quantitative method. In addition, the design used  was quasi-experimental research, and the instrument used a test. The research was taken by using non-random sampling. Moreover, this research was conducted through the following procedures: giving pre-test, applying treatments and giving post-test. The data analyzed and processed by using the statistic data calculation of ANCOVA by SPSS 23 program. The significant was shown by the students post-test mean in experimental class is 76.55 and the mean post-test in control class is 70.55. The result of the statistical hypothesis testing found from p-value was 0.000. It is lower than the level significant of 0.05. If p-value ≤ from the level significant 0.05. It means that H1 was accepted and H0 was rejected. In conclusion, Zimmer twins media can be effective as media teaching to writing ability of narrative text at the eleventh-grade students of MA Yayasan Sirojul IslamSukolilo.The objective of the research to compare of Zimmer twins website tool as digital storytelling than use nondigital in writing text narrative on students writing ability at the eleventh grade of MA  Yayasan Sirojul  Islam Sukolilo 2018/2019 academic year. Zimmer twins media is an animated movie maker based on the website for the students to create their short stories in movies with many emotion, etc. The sample of this research the Eleventh of MA YASI those are XI- 1 class as the experimental class, and the X1-2 class as the control class consisted of 20 students. The method in this research was a quantitative method. In addition, the design used  was quasi-experimental research, and the instrument used a test. The research was taken by using non-random sampling. Moreover, this research was conducted through the following procedures: giving pre-test, applying treatments and giving post-test. The data analyzed and processed by using the statistic data calculation of ANCOVA by SPSS 23 program. The significant was shown by the students post-test mean in experimental class is 76.55 and the mean post-test in control class is 70.55. The result of the statistical hypothesis testing found from p-value was 0.000. It is lower than the level significant of 0.05. If p-value ≤ from the level significant 0.05. It means that H1 was accepted and H0 was rejected. In conclusion, Zimmer twins media can be effective as media teaching to writing ability of narrative text at the eleventh-grade students of MA Yayasan Sirojul IslamSukolilo.